2015
DOI: 10.1016/j.aninu.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sources and their effects on animal production and environmental sustainability

Abstract: Animal agriculture has been an important component in the integrated farming systems in developing countries. It serves in a paramount diversified role in producing animal protein food, draft power, farm manure as well as ensuring social status-quo and enriching livelihood. Ruminants are importantly contributable to the well-being and the livelihood of the global population. Ruminant production systems can vary from subsistence to intensive type of farming depending on locality, resource availability, infrastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 34 publications
(67 reference statements)
3
61
0
5
Order By: Relevance
“…Positive effects of plant containing CT and SP on daily gain and milk production have been demonstrated in the previous studies, as well as a protective effect on dietary protein in the rumen in order to promote duodenal absorption, minimize excretion of nitrogen and modify the acetate to propionate ratio in rumen fluid (Anantasook et al., ; Salem et al., , ). Use of CT and SP extract may be commercially available as their cost is currently prohibitive for their routine use in animal production systems (Wanapat, Cherdthong, Phesatcha, & Sungchhang, ). However, research is still required on the optimum sources of CT and SP, the level of CT astringency (chemical composition) and dose rates required to decrease methane and stimulate animal performance (Gunun et al., ; Wanapat, Kang, & Polyorach, ).…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects of plant containing CT and SP on daily gain and milk production have been demonstrated in the previous studies, as well as a protective effect on dietary protein in the rumen in order to promote duodenal absorption, minimize excretion of nitrogen and modify the acetate to propionate ratio in rumen fluid (Anantasook et al., ; Salem et al., , ). Use of CT and SP extract may be commercially available as their cost is currently prohibitive for their routine use in animal production systems (Wanapat, Cherdthong, Phesatcha, & Sungchhang, ). However, research is still required on the optimum sources of CT and SP, the level of CT astringency (chemical composition) and dose rates required to decrease methane and stimulate animal performance (Gunun et al., ; Wanapat, Kang, & Polyorach, ).…”
Section: Introductionmentioning
confidence: 99%
“…Methane production in the rumen represents 2-12% loss of feed energy [2] decreasing the metabolizable energy content of feeds. In addition, production of greenhouse gases from animals and their impact on climate changes are a major concern worldwide [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Knapp et al (2014) observed that increased ether extract content in the diet resulted in decreased CH 4 production per unit of milk produced (kg), according to lipid sources and content. Wanapat et al (2015) verified that unsaturated fatty acids added to ruminant diets reduced gas production due to their toxic effect on the ruminal protozoa that act on fiber digestion, as well as on methanogens, and to the competition generated when hydrogens are employed in the biohydrogenation process of the unsaturated lipid bonds instead of in CH 4 production. Those authors also found that plant extracts can affect ruminal fermentation due to the presence of active secondary metabolites, such as saponins and tannins, which have an effect on methanogens and on the nutrient degradation of the diet.…”
Section: Resultsmentioning
confidence: 99%
“…Non-fibrous carbohydrates may promote changes in the physicochemical conditions of the rumen and in the population of microorganisms (Wanapat et al, 2015). Rumen degradation promotes a pH reduction that may influence the survival of microorganisms, and abrupt changes may interfere in the digestibility of low-quality forages (Castillo-González et al, 2014).…”
Section: Resultsmentioning
confidence: 99%